Cognitive behavioral therapy for patients with mild to moderate depression: Treatment effects and neural mechanisms. (April 2021) - Meng, Yanjun; Li, Hong; Wang, Junjie; Xu, Yong; Wang, Binquan
Abstract: In this study, we combined clinical assessment and magnetic resonance imaging (MRI) techniques to investigate the brain mechanisms in mild to moderate depression (MMD) patients following cognitive behavioral therapy (CBT). Data were collected from 30 MMD patients and 18 healthy controls, and we divided patients into two treatment periods (4 weeks, 8 weeks). Clinical assessment indicated that depression characteristics, as quantified by Hamilton Depression Rating Scale (HAMD), were significantly higher in MMD patients than in healthy controls. At the baseline, MRI data revealed abnormalities in the hippocampus and nucleus accumbens (NAc) of patients with MMD, e.g., smaller gray matter volumes of the hippocampus and nucleus accumbens (NAc), as well as weaker functional connectivity between NAc and the posterior cingulate cortex/precuneus. Moreover, the hippocampus and NAc volumes were negatively correlated with the HAMD scores in MMD patients. After CBT intervention, the HAMD scores decreased, and the structural and functional characteristics of NAc in MMD patients obtained at 8-week were improved; e.g., no significant differences in NAc volume or NAc-based functional connectivity between the two groups. Taken together, our results provided evidence suggesting that CBT is an effective treatment for MMD patients. Alterations of gray matter volume and resting-state functional connectivity after 8 weeks of CBT indicated a potential modulation mechanism in brain structural modifications and functional connectivity plasticity within the NAc in MMD patients. Highlights: Cognitive behavioral therapy (CBT) is an effective treatment for mild to moderate depression (MMD) patients. Nucleus accumbens volume increased in MMD patients after 8-week CBT. Nucleus accumbens-based functional connectivity improved in MMD patients after 8-week CBT.